(untitled) (Nativa, 2018)
Os efeitos da liberação de aleloquímicos de uma espécie sobre outra podem resultar em danos ecológicos aos ecossistemas, como a facilitação de estabilização e povoamento de espécies invasoras. Com este trabalho, objetivou-se avaliar os efeitos alelopáticos de partes vegetais da algaroba, espécie invasora, sobre a emergência e o crescimento inicial de plântulas de jurema-preta, espécie nativa da Caatinga. Prepararam-se extratos aquosos de folhas, cascas e raízes da algaroba, usando 125 g de material vegetal para cada 500 mL de água destilada, nas concentrações 0, 25, 50, 75 e 100%. Foram utilizados tubetes de 55 cm3 preenchidos com solo. Distribuíram-se os tratamentos em delineamento inteiramente casualizado (DIC), com quatro repetições, cada uma com cinco tubetes. Avaliaram-se a porcentagem de emergência, altura, diâmetro do caule, número de folhas e peso seco de folhas, caule, raiz, parte aérea e total. A exceção do extrato de casca a 100% no peso seco total, todos os extratos causaram efeitos deletérios a emergência e plântulas de jurema-preta, sendo o extrato de raiz a 100%, o responsável pela maior redução na porcentagem de emergência, 33%, em compração com o tratamento controle. Palavra-chave: alelopatia, algaroba, invasão biológica, jurema-preta, semiárido. ALLELOPATHIC EFFECT OF AQUEOUS EXTRACTS OF Prosopis juliflora (SW.) DC IN THE EMERGENCE AND INITIAL GROWTH OF Mimosa tenuiflora (WILLD.) Poiret SEEDLINGS ABSTRACT: The effects of allelochemicals release of one species over another may result in ecological damage to ecosystems, such as facilitating the stabilization and settlement of invasive species. The objective of this study was to evaluate the allelopathic potential of different plant parts of Prosopis juliflora, invasive species, emergence and early growth of Mimosa tenuiflora, native species of Caatinga. The aqueous extracts of leaves, barks and roots from the algaroba were prepared at a ratio of 125 g of plant material to 500 ml of distilled water, diluted at concentrations of 0, 25, 50, 75 and 100%. For emergence and early growth, tubes were used in 55 cm3, with application of the extracts every 15 days. The treatments were also distributed in DIC, with four replications and five tubes by repetition. We evaluated the percentage of emergence, plant height, stem diameter, number of leaves, dry weight of leaves, stem, root, aerial and total parts. With the exception of 100% bark extract on the total dry weight of all the extracts caused deleterious effects the emergence and seedling jurema-preta, being the extract of root to 100%, responsible for the greater reduction in the percentage of emergency, 33%, in purchase with the control treatment. Keywords: allelopathy, algaroba, biological invasion, jurema-preta, semiarid.